Financial Challenges and Opportunities In The Maritime Industry: Insights From Expert Perspectives - Indah Anggoro Putri; Muhammad Zilal Hamzah; Eleonora Sofilda (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research investigates the intricate landscape of financial challenges and opportunities in the maritime industry through the lens of expert perspectives in economics, management, and maritime operations. Drawing on qualitative insights from industry leaders and scholars, the study analyses key economic indicators such as GDP growth rates, inflation, interest rates, and trade balances, highlighting their profound impact on global shipping dynamics. The findings reveal pervasive challenges including economic volatility, regulatory compliance burdens, and sustainability pressures, which necessitate strategic responses for financial resilience and operational sustainability. Strategic recommendations are delineated to address these challenges effectively, advocating for enhanced risk management strategies, investment in technological innovation, adoption of sustainable practices, collaborative industry partnerships, and capacity building in talent development. These insights are crucial for maritime stakeholders aiming to navigate economic uncertainties and regulatory complexities while advancing towards sustainable growth and competitiveness in the global maritime economy.